Wake wave excited by the sequence of relativistic electron bunches: initial stage - Vynnyk, O.K.; Anisimov, I.O. (Вопросы атомной науки и техники, 2018)
This report is devoted to the study of initial stage of the wake wave excited by the sequence of the short
relativistic electron bunches. We used the modernized simulation package described in and based on the particle-incell method. Spectra for electromagnetic field components were obtained for the single bunch and both for nonresonant and resonant bunches` sequences. Стаття присвячена вивченню початкової стадії зростання кільватерної хвилі, збудженої послідовністю
коротких релятивістських електронних згустків. Використовується модернізований програмний пакет
моделювання методом крупних частинок. Отримано спектри компонент електромагнітного поля для
одиночного згустка, для нерезонансної та резонансної послідовностей згустків. Статья посвящена изучению начальной стадии возрастания кильватерной волны, возбужденной
последовательностью коротких релятивистских электронных сгустков. Используется модернизированный
программный пакет моделирования методом крупных частиц. Получены спектры компонент
электромагнитного поля для одиночного сгустка, для нерезонансной и резонансной последовательностей
сгустков.